Anesthetic management of thoracoscopic pulmonary wedge resection with a giant tracheal diverticulum in the carina: a case report and review of the literature. Issue 11 (November 2021) - Huang, Xiao; Sun, Yuan; Lin, Dandan; Wei, Changewi; Wu, Anshi; Gao, Chao
A tracheal diverticulum (TD) is a rare disease that is usually diagnosed as an incidental finding on thoracic computed tomography or bronchoscopy. TDs can be classified as congenital or acquired. In patients undergoing surgery, TDs can result in difficult intubation, difficult ventilation, pneumothorax, and other complications. We herein report a case of anesthetic management of thoracoscopic pulmonary wedge resection in a patient with a giant TD in the carina. Intraoperative double-lumen intubation and single-lung ventilation were challenging to perform. Fiberoptic-guided intubation was helpful, and intraoperative management was tailored to avoid diverticulum rupture. In this report, we also review complications related to TD in surgical patients undergoing mechanical ventilation. Ventilation is one of the most prominent anesthetic challenges. The close collaboration of the entire medical team was a key factor in the successful management of this rare case.